Analisis Pengaruh Kondisi Keuangan Perusahaan, Kualitas Auditor, Opini Audit Tahun Sebelumnya Dan Ukuran Perusahaan Terhadap Opini Audit Going Concern (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2012-2014) - Heryanto, Agus, Drs. Atwal Arifin, AK., M.Si., CA (2016)
This research is a study that tested the effect of Company Financial Condition, Auditor Quality, Audit Opinions Of Prior Year, the Company's Growth of the acceptance of Going Concern in the manufacturing companies listed at Indonesia Stock Exchange. In the study, researchers used purposive sampling and sample size to obtain a sample of 90 manufacturing companies listed on the Stock Exchange in the year 2012-2014. The method on analysis used was logistic regression. The results of this study indicate Company Auditor Quality affect on the acceptance of going concern opinion while Company Financial Condition, Audit Opinions Of Prior Year, and Company's Growth do not affect the going concern opinion.